Spectroscopic studies on glassy Ni(II) and Co(II) polyphosphate coacervates - Silva, Mauricio A. P.; Franco, Douglas F.; Brandao, Adilson R.; Barud, Hernane [UNESP]; Dias Filho, Francisco A.; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP]; de Oliveira, Luiz F. C. (Elsevier B.V. Sa, 2010)
Transparent amorphous bulk materials have been prepared through the coacervation process of sodium polyphosphate and Ni(2+) and Co(2+) chloride solutions. Structural and spectroscopic properties were analyzed by X-ray diffraction, thermogravimetric analysis, UV-vis, infrared and Raman spectroscopic techniques. Different optical properties and water absorption tendencies were observed for the polyphosphate coacervates. The symmetric P-O(b) and P-O(t) stretching modes on the Raman spectra for the coacervates and the sodium polyphosphate revealed the coordination processes of the polyphosphate chains to the metal ions, including the effects of the water coordination outside the polyphosphate cages, connecting the adjacent chains. Based on data collected from the electronic spectra, these materials can present important technological applicability. Being transparent materials, these glasses can be used as absorption filters with pass-band between 600 and 500 nm for the Ni coacervate, and above 600 nm for the Co coacervate. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Amorphous materials; Glasses; Raman spectroscopy and scattering; Optical properties